Isn't she great [videorecording (DVD)] - Lobell, Mike; Lindenlaub, Karl Walter; Malkin, Marry; Bacharach, Burt; Bergman, Andrew; Rudnick, Paul; Midler, Bette; Lane, Nathan, 1956-; Channing, Stockard; Pierce, David Hyde; Cleese, John; Korda, Michael, 1933- (Universal Studios, 2000)
Comedy based on the life of best-selling novelist Jacqueline Susann.